An assessment of media contribution to behavior change and HIV prevention in Nigeria (2017)
This chapter explores media influence on behaviour change and its implication for HIV prevention programmes in Nigeria. Using the agenda setting, and the uses and gratifications theories, it analyzes how the media set agenda for public opinion and the gratification that audience receive from media information vis-a-vis behaviour change initiatives in reducing HIV epidemic in Nigeria. The chapter through a descriptive and literature review approach assesses effective communication framework for behaviour change and some of the factors contributing to HIV prevalence in Nigeria. The chapter sums up case studies of interventions that have documented the effectiveness of the media in HIV prevention initiatives. The chapter concludes on the positive influence of media intervention in sexual behaviour change programmes but notes that behaviour change still lies with individual decisions. Therefore it recommends other forms of communication like interpersonal communication, community mobilization and advocacy to support media strategies for effective HIV prevention initiatives in Nigeria.